2002
DOI: 10.1038/sj.bjc.6600502
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of somatic mutations in the FH/multiple cutaneous leiomyomatosis gene in sporadic leiomyosarcomas and uterine leiomyomas

Abstract: Germline mutations in the fumarate hydratase gene at 1q43 predispose to dominantly inherited skin and uterine leiomyomata and leiomyosarcomas. The enzyme, which is a component of the tricarboxylic acid cycle, acts as a tumour suppressor. To evaluate fumarate hydratase in respective sporadic tumours, we analysed a series of 26 leiomyosarcomas and 129 uterine leiomyomas (from 21 patients) for somatic mutations in fumarate hydratase and allelic imbalance around 1q43. None of the 26 leiomyosarcomas harboured somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 12 publications
(2 reference statements)
1
38
0
2
Order By: Relevance
“…Seventeen percent of tumors showed AI at 1q43. Barker et al (2002) reported AI at 1q in half of the analyzed ULMS, but in some of the cases AI was not confined to the vicinity of FH. 23 In addition, in previous CGH analyses of ULMSs, chromosomal gains at 1q have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen percent of tumors showed AI at 1q43. Barker et al (2002) reported AI at 1q in half of the analyzed ULMS, but in some of the cases AI was not confined to the vicinity of FH. 23 In addition, in previous CGH analyses of ULMSs, chromosomal gains at 1q have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Barker et al (2002) reported AI at 1q in half of the analyzed ULMS, but in some of the cases AI was not confined to the vicinity of FH. 23 In addition, in previous CGH analyses of ULMSs, chromosomal gains at 1q have been reported. [3][4][5] Thus, it is possible that another yet unidentified gene at 1q is involved in tumorigenesis of ULMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die häufiger vorkommenden, in der Regel größeren (>5 cm), selten schmerzhaften, tief dermalen bis subkutan gelegenen LMS weisen eine 50%ige Lokalrezidivrate und eine hä-matogene Metastasierungshäufigkeit von 30-60% auf [2]; 25% metastasieren lymphogen [4]. Häufigster Metastasierungsort sind die Lungen, gefolgt von Leber und Skelett [5].…”
Section: Diskussionunclassified